Anaerobic microbial fuel cell treating combined industrial wastewater: Correlation of electricity generation with pollutants. (January 2016) - Abbasi, Umara; Jin, Wang; Pervez, Arshid; Bhatti, Zulfiqar Ahmad; Tariq, Madiha; Shaheen, Shahida; Iqbal, Akhtar; Mahmood, Qaisar
Highlights: A dual chamber MFC was operated under laboratory conditions treating industrial wastewaters. The treatment efficiency for COD in MFC ranged 85–90%. The maximum voltage was 890 mV with columbic efficiency of 5184.7 C. Positive significant co-relation was observed between COD concentration and voltage. Abstract: Microbial fuel cell (MFC) is a new technology that not only generates energy but treats wastewater as well. A dual chamber MFC was operated under laboratory conditions. Wastewater samples from vegetable oil industries, metal works, glass and marble industries, chemical industries and combined industrial effluents were collected and each was treated for 98 h in MFC. The treatment efficiency for COD in MFC was in range of 85–90% at hydraulic retention time (HRT) of 96 h and had significant impact on wastewater treatment as well. The maximum voltage of 890 mV was generated when vegetable oil industries discharge was treated with columbic efficiency of 5184.7 C. The minimum voltage was produced by Glass House wastewater which was 520 mV. There was positive significant co-relation between COD concentration and generated voltage. Further research should be focused on the organic contents of wastewater and various ionic species affecting voltage generation in MFC.